Preparation method of silicon-carbon composite material and lithium ion battery containing composite material

By mixing the carbon-silicon precursor material, metal lithium and magnesium oxide to form magnesium silicate and lithium silicate compounds, sintering and deposition treatment, forming lithium-magnesium co-doped silicon-carbon composite materials, the problems of large electronic impedance and silicon grain expansion in lithium-ion batteries are solved, and efficient fast charging and long-term circulation performance are achieved.

CN119852357APending Publication Date: 2025-04-18TIMES NEW ENERGY INVESTMENT (HAINAN) PARTNERSHIP (LLP)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960444.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the electron impedance of the porous carbon matrix is ​​large, resulting in poor electronic conductivity and affecting fast charging performance; at the same time, silicon grains are prone to grow larger during high-temperature cracking, resulting in volume expansion, affecting the first efficiency and long-term circulation performance of the battery.

Method used

By mixing the carbon-silicon precursor material, metal lithium and magnesium oxide to form magnesium silicate and lithium silicate compounds, sintering and deposition treatment, forming a lithium-magnesium co-doped silicon-carbon composite material, reducing the expansion of nano-silicon, improving structural stability and fast charging performance.

Benefits of technology

It improves the first-time efficiency and circulation performance of lithium-ion batteries, reduces irreversible capacity, and improves fast charging performance and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852357A_ABST
    Figure CN119852357A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a preparation method of a silicon-carbon composite material and a lithium ion battery containing the composite.The preparation method of the silicon-carbon composite material comprises the steps that porous carbon is transferred into a tubular furnace for heating treatment, and a silicon-carbon precursor material is obtained; mixing the silicon-carbon precursor material, metal lithium and magnesium oxide powder in a protective atmosphere to obtain a mixed material; carrying out sintering treatment on the mixed material; and carrying out deposition treatment on the sintered mixed material to precipitate amorphous carbon on the surface of the sintered mixed material to obtain the silicon-carbon composite material. According to the preparation method, the carbon-silicon precursor material, the metal lithium and the magnesium oxide are mixed, so that the structural stability and the first efficiency of the material are improved, meanwhile, the expansion of nano silicon can be reduced, and the first efficiency and the cycle performance of the silicon-carbon composite material are improved; meanwhile, the impedance of the porous carbon is reduced by metal doping, and the fast charging performance of the silicon-carbon composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a silicon-carbon composite material and a lithium-ion battery comprising the composite material. Background Art

[0002] The gas silane cracking method is to prepare silicon-carbon materials by cracking silane gas to generate nano-silicon and depositing it in porous carbon. It is used in high specific energy density lithium-ion batteries due to its advantages such as high energy density, low expansion and good cycle performance.

[0003] However, due to the large electronic impedance of the porous carbon matrix, the electronic conductivity is poor, resulting in deviations in the fast charging performance. In addition, in the process of preparing silicon-carbon materials by the silane cracking method, the silicon grains tend to become larger under the high cracking temperature environment, thereby causing volume expansion. This expansion is not only slightly high, but also causes changes in the material structure, thereby affecting the battery's initial efficiency and long-term cycle performance. Summary of the invention

[0004] Based on this, the embodiments of the present application provide a method for preparing a silicon-carbon composite material and a lithium-ion battery comprising the composite material, aiming to improve the structural stability of the silicon-carbon composite material and its initial efficiency by mixing a carbon-silicon precursor material, metallic lithium and magnesium oxide to form magnesium silicate and lithium silicate compounds. At the same time, the pre-formation of magnesium silicate can reduce the expansion of nano-silicon, improve the initial efficiency of the silicon-carbon composite material and its cycle performance, and at the same time, metal doping reduces the impedance of porous carbon and improves the fast charging performance of the silicon-carbon composite material.

[0005] A first aspect of the present application provides a method for preparing a silicon-carbon composite material, the method comprising:

[0006] The porous carbon is transferred to a tube furnace for temperature treatment to obtain a silicon-carbon precursor material;

[0007] Under a protective atmosphere, the silicon-carbon precursor material, metallic lithium and magnesium oxide powder are mixed to obtain a mixed material;

[0008] sintering the mixed material;

[0009] The sintered mixed material is subjected to a deposition treatment to precipitate amorphous carbon on the surface of the sintered mixed material to obtain a silicon-carbon composite material.

[0010] Optionally, the step of transferring the porous carbon to a tube furnace for heating to obtain a silicon-carbon precursor material comprises:

[0011] The tube furnace is evacuated to 0.09 MPa, and chlorosilane gas is introduced into the tube furnace after evacuation and the temperature is raised to 300-500° C. The pressure of the cavity of the tube furnace after evacuation is maintained at 0.1-1 MPa and kept warm for 1-6 hours to obtain a silicon-carbon precursor material.

[0012] Optionally, the method further comprises:

[0013] The chlorosilane is transferred to a reaction kettle and evacuated to a pressure of 0.1 to 0.5 MPa, and then the chlorosilane is heated to 100 to 300° C. to obtain the chlorosilane gas.

[0014] Optionally, the mass ratio of the porous carbon to the chlorosilane is 100:(400-1000).

[0015] Optionally, the chlorosilane is one of propenyltrichlorosilane, trichlorosilane, tetrachlorosilane and dimethylchlorosilane.

[0016] Optionally, the mass ratio of the silicon-carbon precursor material, the metallic lithium and the magnesium oxide powder is 100:(1-5):(1-5).

[0017] Optionally, the sintering the mixed material includes:

[0018] The mixed material is sintered at a temperature of 900 to 1200°C.

[0019] Optionally, the depositing process on the sintered mixed material includes:

[0020] Through the vapor deposition method, a carbon source gas is introduced and deposited at a temperature of 700 to 1000° C. for 1 to 6 hours.

[0021] Optionally, the carbon source gas includes one of methane, acetylene and ethylene.

[0022] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, characterized in that the negative electrode includes a silicon-carbon composite material prepared by the preparation method of the silicon-carbon composite material described in any one of the first aspects above.

[0023] The present application provides a method for preparing a silicon-carbon composite material, which is obtained by transferring porous carbon to a tube furnace for temperature treatment; mixing the silicon-carbon precursor material, metallic lithium and magnesium oxide powder under a protective atmosphere to obtain a mixed material; sintering the mixed material; and depositing the sintered mixed material to precipitate amorphous carbon on the surface of the sintered mixed material to obtain a silicon-carbon composite material. In the present application, first, the porous carbon is subjected to a temperature treatment in a tube furnace, and a pyrolysis reaction can be performed under a controlled atmosphere, thereby depositing nano-silicon in the porous carbon to obtain a carbon-silicon precursor material; then, under a protective atmosphere, the carbon-silicon precursor material, metallic lithium and magnesium oxide are mixed to form magnesium silicate. The lithium silicate compound, i.e., the mixed material, can prevent the material from oxidation and maintain the activity and purity of the material. The addition of metallic lithium can improve the electrochemical activity of the material, while magnesium oxide can act as a stabilizer to enhance the structural stability of the material, which is beneficial to improving the first efficiency. At the same time, the pre-formation of magnesium silicate can reduce the expansion of nano-silicon, improve the first efficiency and cycle performance of the silicon-carbon composite material, and metal doping reduces the impedance of porous carbon to improve the fast charging performance of the silicon-carbon composite material; secondly, the sintering treatment helps the combination of the silicon-carbon precursor material with metallic lithium and magnesium oxide; finally, the deposition treatment can form a layer of amorphous carbon on the surface of the sintered mixed material, which can improve the electrical conductivity of the material, reduce the deposition of the surface solid electrolyte interface (Solid Electrolyte Interphase, SEI) film, and effectively inhibit the volume effect, thereby obtaining a higher first efficiency and a smaller irreversible capacity. In addition, the coating of amorphous carbon can also improve the structural stability and cycle performance of the material, and reduce the influence of the volume change of silicon particles during the charging and discharging process on the material structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 1 is a schematic flow chart of a method for preparing a silicon-carbon composite material provided in an embodiment of the present application;

[0026] Figure 2 This is a SEM image of the silicon-carbon composite material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other in the absence of conflict. The present invention will be described in detail below in conjunction with the embodiments.

[0028] An embodiment of the present application provides a method for preparing a silicon-carbon composite material, comprising transferring porous carbon to a tubular furnace for temperature treatment to obtain a silicon-carbon precursor material; mixing the silicon-carbon precursor material, metallic lithium and magnesium oxide powder under a protective atmosphere to obtain a mixed material; sintering the mixed material; and depositing the sintered mixed material to precipitate amorphous carbon on the surface of the sintered mixed material to obtain a silicon-carbon composite material.

[0029] First, the porous carbon is heated in a tubular furnace to undergo a pyrolysis reaction under a controlled atmosphere, thereby depositing nanosilicon in the porous carbon to obtain a carbon-silicon precursor material; then, under a protective atmosphere, the carbon-silicon precursor material, metallic lithium and magnesium oxide are mixed to form a magnesium silicate-lithium silicate compound, i.e., a mixed material, which can prevent oxidation of the material and maintain the activity and purity of the material. The addition of metallic lithium can improve the electrochemical activity of the material, while magnesium oxide can act as a stabilizer to enhance the structural stability of the material, which is beneficial to improving the first efficiency. At the same time, the pre-formation of magnesium silicate can reduce the expansion of nano-silicon, improve the first efficiency and cycle performance of the silicon-carbon composite material, and metal doping reduces the impedance of porous carbon to improve the fast charging performance of the silicon-carbon composite material; secondly, the sintering treatment helps the combination of the silicon-carbon precursor material with metallic lithium and magnesium oxide; finally, the deposition treatment can form a layer of amorphous carbon on the surface of the sintered mixed material, which can improve the electrical conductivity of the material, reduce the deposition of the surface solid electrolyte interface (Solid Electrolyte Interphase, SEI) film, and effectively inhibit the volume effect, thereby obtaining a higher first efficiency and a smaller irreversible capacity. In addition, the coating of amorphous carbon can also improve the structural stability and cycle performance of the material, and reduce the influence of the volume change of silicon particles during the charging and discharging process on the material structure.

[0030] See also Figure 1 , which is a schematic flow chart of a method for preparing a silicon-carbon composite material provided in an embodiment of the present application. The method for preparing the silicon-carbon composite material comprises the following steps.

[0031] S1, transferring the porous carbon to a tube furnace for temperature treatment to obtain a silicon-carbon precursor material.

[0032] The porous carbon is subjected to a temperature-raising treatment in a tube furnace, and a pyrolysis reaction can be performed under a controlled atmosphere, thereby depositing nano-silicon in the porous carbon to obtain a carbon-silicon precursor material.

[0033] The tube furnace may be a vacuum tube furnace.

[0034] In a preferred embodiment, the step of transferring the porous carbon to a tube furnace for heating to obtain a silicon-carbon precursor material comprises:

[0035] The tube furnace is evacuated to 0.09 MPa, and chlorosilane gas is introduced into the tube furnace after evacuation and the temperature is raised to 300-500° C. The pressure of the cavity of the tube furnace after evacuation is maintained at 0.1-1 MPa and kept warm for 1-6 hours to obtain a silicon-carbon precursor material.

[0036] The above-mentioned process parameter conditions include but are not limited to the above-mentioned ranges. Limiting them within the above-mentioned ranges is beneficial to the reaction efficiency and uniformity between the chlorosilane gas and the silicon-carbon precursor material, and is beneficial to the uniform distribution and combination of silicon and carbon in the silicon-carbon precursor material, thereby optimizing the electrochemical properties and structural stability of the material, ensuring that the material fully reacts to form a stable silicon-carbon precursor structure, while avoiding the degradation of material performance due to excessive insulation time.

[0037] In a preferred embodiment, the method further comprises:

[0038] The chlorosilane is transferred to a reaction kettle and evacuated to a pressure of 0.1 to 0.5 MPa, and then the chlorosilane is heated to 100 to 300° C. to obtain the chlorosilane gas.

[0039] The above process parameter conditions include but are not limited to the above ranges. Limiting them within the above ranges is beneficial to improving the conversion rate of chlorosilane, thereby improving the reaction efficiency, ensuring the uniformity of the reaction, and avoiding local overheating or insufficient reaction.

[0040] Among them, chlorosilane is chlorosilane liquid.

[0041] In the related art, the gas silane cracking method is used to prepare silicon-carbon precursor materials, which has high requirements on the environment. The high cracking temperature causes the silicon grains to be larger and expand slightly higher. At the same time, the H2 tail gas produced by the cracking of SiH4 poses a great safety hazard when encountering air, making it difficult to mass produce and the manufacturing cost is high.

[0042] Since liquid chlorosilane contains chlorine atoms, chlorine doping is achieved after cracking, so that the resulting material has the advantages of low impedance, low reaction temperature, and low safety hazards. The cracking of chlorosilane under a certain vacuum condition can improve the fast charging performance of silicon-carbon materials. This embodiment uses liquid silane to gasify and crack under a certain vacuum condition to generate gaseous silane. Compared with gaseous silane (SiH4), it has the advantages of low cracking temperature, low cost, and high safety factor. The vaporized chlorosilane is deposited in porous carbon, which can be doped with chlorine to improve the electronic conductivity of the material, improve the shortcomings of the porous carbon itself, such as poor electronic conductivity, and further improve the fast charging performance.

[0043] In a preferred embodiment, the mass ratio of the porous carbon to the chlorosilane is 100:

[0044] (400~1000).

[0045] Compared with other ranges, limiting the mass ratio of the two within the above range is conducive to more effective adsorption and filling of chlorosilane gas molecules, improving the efficiency of silicon deposition, and ensuring that silicon is uniformly deposited in the porous carbon to form a stable structure, which can reduce the material expansion rate, improve the first coulomb efficiency, increase the first discharge capacity, and improve the capacity retention rate after long-term cycling, and ensure the reasonable controllability of the silicon deposition amount, which helps to improve the conductivity of the composite material, thereby helping to improve the rate performance of the battery.

[0046] In a preferred embodiment, the chlorosilane is one of propenyltrichlorosilane, trichlorosilane, tetrachlorosilane and dimethylchlorosilane.

[0047] S2, under a protective atmosphere, mixing the silicon-carbon precursor material, metallic lithium and magnesium oxide powder to obtain a mixed material.

[0048] The mixed material may include magnesium silicate and lithium silicate compounds.

[0049] The protective atmosphere may be an inert atmosphere, such as an argon inert atmosphere. In the inert atmosphere, the silicon-carbon precursor material, metal lithium and magnesium oxide powder are mixed uniformly to obtain a mixed material.

[0050] In a preferred embodiment, the mass ratio of the silicon-carbon precursor material, the metallic lithium and the magnesium oxide powder is 100:(1-5):(1-5).

[0051] Compared with other ranges, limiting the mass ratio of the two within the above range can effectively avoid agglomeration and sintering, maintain the morphology of the silicon-carbon precursor material, and is beneficial to improving the reversible specific capacity and cycle stability of the silicon-carbon precursor material, improving structural stability, conductivity, and controlling volume expansion, thereby improving the cycle performance and rate performance in lithium-ion batteries.

[0052] S3, sintering the mixed material.

[0053] The sintering process helps to bond the silicon-carbon precursor material with the metallic lithium and magnesium oxide.

[0054] In a preferred embodiment, the sintering process of the mixed material comprises:

[0055] The mixed material is sintered at a temperature of 900 to 1200°C.

[0056] The temperature of the sintering treatment includes but is not limited to the above range. Limiting it within the above range can avoid local intense reactions and excessively high temperatures, which will lead to a sharp increase in the size of silicon crystals and agglomeration of magnesium oxide into larger particles, thereby helping to improve the initial efficiency.

[0057] S4, performing a deposition process on the sintered mixed material to precipitate amorphous carbon on the surface of the sintered mixed material to obtain a silicon-carbon composite material.

[0058] The silicon-carbon composite material is lithium-magnesium co-doped silicon-carbon material.

[0059] The deposition of the amorphous carbon layer helps to alleviate the volume expansion of silicon during the charging and discharging process. The hollow structure reserves space for the volume expansion of silicon, ensuring that the structure of the surface carbon layer is not destroyed, thereby obtaining a stable SEI film. It not only enhances the structural stability of the silicon-carbon composite material and reduces the structural damage caused by volume changes during the charging and discharging process, but also improves the electrochemical properties of the silicon-carbon composite material, including specific capacity, cycle stability and rate performance.

[0060] In a preferred embodiment, the deposition process of the sintered mixed material comprises:

[0061] Through the vapor deposition method, a carbon source gas is introduced and deposited at a temperature of 700 to 1000° C. for 1 to 6 hours.

[0062] The temperature and time of the deposition process include but are not limited to the above ranges. Limiting them within the above ranges can increase the chemical reaction rate between the carbon source gas and the sintered mixed material, which is beneficial to improving the deposition rate and efficiency, and accurately controlling the thickness of the deposition layer.

[0063] Vapor deposition is a process in which a gaseous substance reacts chemically on a solid surface at a certain temperature to form a solid deposited film on the surface. Vapor deposition can include physical vapor deposition (PVD) and chemical vapor deposition (CVD). In the CVD process, the reaction gas diffuses to the surface of the workpiece and is adsorbed, and various substances adsorbed on the surface of the workpiece undergo surface chemical reactions, and the generated material points gather into crystals and grow. The gas products produced in the surface chemical reactions detach from the surface of the workpiece and return to the gas phase, and the elements interdiffusion occurs at the interface between the deposited layer and the substrate to form a coating. PVD is a process in which metals, alloys or compounds are evaporated (or sputtered) in a vacuum chamber, so that these gas phase atoms or molecules are deposited on the surface of the workpiece under certain conditions.

[0064] In a preferred embodiment, the carbon source gas includes one of methane, acetylene and ethylene.

[0065] The present application also provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, and the negative electrode includes a silicon-carbon composite material prepared by the preparation method of the above-mentioned silicon-carbon composite material provided in the present application.

[0066] The silicon-carbon composite material uses the formed lithium magnesium silicate to reduce its irreversible capacity and improve the first efficiency. At the same time, metal doping reduces its impedance and improves the fast charging performance of the material. At the same time, liquid chlorosilane is gasified to generate gaseous chlorosilane to dope chlorine-porous carbon to improve the electronic conductivity of the material and improve the rate performance. The resulting silicon-carbon composite material can be applied to lithium-ion batteries to improve the rate performance, first efficiency and high-temperature storage performance of silicon-carbon materials.

[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0068] Example 1

[0069] (1) 100 g of porous carbon was transferred to a vacuum tube furnace A and evacuated to 0.09 MPa; at the same time, 600 g of acryltrichlorosilane liquid was evacuated to 0.4 MPa in a reactor B, and then heated to 200 ° C to obtain chlorosilane gas; then the chlorosilane gas was introduced from the reactor B into the vacuum tube furnace A, and the temperature was raised to 400 ° C, and the pressure of the cavity was maintained at 0.5 MPa, and the temperature was kept for 3 hours to obtain a silicon-carbon precursor material;

[0070] (2) Under an argon inert atmosphere, 100 g of silicon-carbon precursor material, 3 g of metallic lithium and 3 g of magnesium oxide powder were mixed evenly;

[0071] (3) then sintered at 1000°C for 3h;

[0072] (4) Then, methane gas was introduced through a vapor phase deposition method and deposited at a temperature of 900° C. for 3 h to obtain a lithium-magnesium co-doped silicon-carbon material.

[0073] Example 2

[0074] (1) 100 g of porous carbon was transferred to a vacuum tube furnace A and evacuated to 0.09 MPa; at the same time, 400 g of chlorosilane liquid was evacuated to 0.1 MPa in a reaction kettle B, and then heated to 100 ° C to obtain chlorosilane gas; then the chlorosilane gas was passed from the reaction kettle B into the vacuum tube furnace A, and the temperature was raised to 300 ° C, and the pressure of the cavity was maintained at 0.1 MPa, and the temperature was kept for 6 hours to obtain a silicon-carbon precursor material;

[0075] (2) Under an argon inert atmosphere, 100 g of silicon-carbon precursor material, 1 g of metallic lithium and 1 g of magnesium oxide powder were mixed evenly;

[0076] (3) then sintered at 900°C for 6h;

[0077] (4) Then, acetylene gas was introduced through a vapor deposition method and deposited at a temperature of 700° C. for 6 hours to obtain a lithium-magnesium co-doped silicon-carbon material.

[0078] Example 3

[0079] (1) 100 g of porous carbon was transferred to a vacuum tube furnace A and evacuated to 0.09 MPa; at the same time, 1000 g of chlorosilane liquid was evacuated to 0.5 MPa in a reactor B, and then heated to 300 ° C to obtain chlorosilane gas; then, the chlorosilane gas was introduced from the reactor B into the vacuum tube furnace A, and the temperature was raised to 500 ° C, and the pressure of the cavity was maintained at 1 MPa, and the temperature was kept for 1 hour to obtain a silicon-carbon precursor material;

[0080] (2) Under an argon inert atmosphere, 100 g of silicon-carbon precursor, 5 g of metallic lithium and 5 g of magnesium oxide powder were mixed evenly;

[0081] (3) then sintering at 1200°C for 1h;

[0082] (4) Then, ethylene gas was introduced through a vapor phase deposition method and the deposition was carried out at a temperature of 1000° C. for 1 hour to obtain a lithium-magnesium co-doped silicon-carbon material.

[0083] Comparative Example 1

[0084] The difference from Example 1 is that no metallic lithium and magnesium oxide powder are added, and 100 g of the silicon-carbon precursor is directly sintered at a temperature of 1000° C. for 3 h.

[0085] Comparative Example 2

[0086] (1) 100 g of porous carbon was transferred to a vacuum tube furnace A, and then 600 g of acryltrichlorosilane liquid was added and dispersed evenly, and then the mixture was evacuated to 0.5 MPa, and the temperature was raised to 400 ° C and kept for 3 h to obtain a silicon-carbon precursor material;

[0087] (2) Under an argon inert atmosphere, 100 g of silicon-carbon precursor, 3 g of metallic lithium and 3 g of magnesium oxide powder were mixed evenly;

[0088] (3) then sintered at 1000°C for 3h;

[0089] (4) Then, methane gas was introduced through a vapor phase deposition method and deposited at a temperature of 900° C. for 3 h to obtain a lithium-magnesium co-doped silicon-carbon material.

[0090] Test conditions

[0091] The lithium-magnesium co-doped silicon-carbon materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the testing method was as follows:

[0092] (1) SEM test

[0093] Figure 2 This is a SEM picture of the lithium-magnesium co-doped silicon-carbon material prepared in Example 1. It can be seen from the figure that the material has a granular structure with a reasonable size distribution and a particle size between 5 and 10 μm.

[0094] (2) Physical and chemical properties and button battery testing

[0095] The lithium-magnesium co-doped silicon-carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for particle size, tap density, specific surface area, silicon grains, Ph, metal content (lithium and magnesium), powder resistivity, specific capacity and first efficiency.

[0096] Test Method

[0097] The powder resistivity of lithium-magnesium co-doped silicon-carbon material powder is tested using a four-probe tester, and other test items are tested in accordance with GB / T 38823-2020 "Silicon Carbon".

[0098] The lithium-magnesium co-doped silicon-carbon materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 are respectively used as negative electrode materials for lithium-ion batteries to be assembled into button batteries A1, A2, A3, B1, and B2; the preparation method thereof is as follows: a binder, a conductive agent, and a solvent are added to the negative electrode material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain the obtained battery. The binder used is LA132 binder, the conductive agent (SP), the negative electrode material is the negative electrode material (i.e., lithium-magnesium co-doped silicon-carbon material) prepared in Examples 1 to 3 and Comparative Examples 1 to 2, respectively, the solvent is double distilled water, and the ratio is: negative electrode material: SP: LA132: double distilled water = 90g: 5g: 4g: 220mL, and a negative electrode plate is prepared; the electrolyte is LiPF6 / ethylene carbonate (EC) + diethyl carbonate (DEC) (volume ratio 1:1, concentration 1.3mol / L), the metal lithium sheet is the counter electrode, and the diaphragm is polyethylene (PE). The simulated battery assembly is carried out in an argon-filled glove box, and the electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester. The charge and discharge voltage range is 0.00V to 2.0V, and the charge and discharge rate is 0.1C. The rate (1C, 0.1C) and cycle performance (0.1C / 0.1C, 100 times) of the button cell were also tested. The test results are shown in Table 1.

[0099]

[0100] Table 1

[0101] From the test results shown in Table 1, it can be seen that the lithium-magnesium co-doped silicon-carbon materials prepared in Examples 1 to 3 have high first efficiency and rate performance. The reason is that by mixing metallic lithium with magnesium oxide to form magnesium silicate and lithium silicate compounds, the structural stability of the material is improved, the first efficiency is improved, and the cycle performance is improved.

[0102] (3) Soft pack battery

[0103] The lithium-magnesium co-doped silicon-carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are used to prepare negative electrode sheets, and the ternary materials (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) as the positive electrode, LiPF6 (solvent is EC+DEC, volume ratio 1:1, concentration 1.3 mol / l) as the electrolyte, and celegard2400 as the separator to prepare 5Ah soft pack batteries C1, C2, C3 and D1, D2, that is, to obtain ternary soft pack lithium batteries. The test results are shown in Tables 2 and 3.

[0104] Rate performance

[0105] The rate performance of the soft-pack battery was tested with a charge and discharge voltage range of 2.5-4.2V and a temperature of 25±3.0℃. The batteries were charged at 1.0C, 3.0C, 5.0C, 10.0C, and 20.C, and discharged at 1.0C.

[0106]

[0107] Table 2

[0108] According to the test results of rate performance shown in Table 2, the rate charging performance of the soft-pack batteries in Examples 1 to 3 is significantly better than that of the comparative example, that is, the charging time is shorter. The reason for this is that in the examples, the electronic impedance of the material is reduced by doping with magnesium and lithium metals with electronic conductivity. At the same time, chlorosilane vaporization and deposition in porous carbon can be used for chlorine doping to improve the electronic conductivity of the material and thus improve the fast charging performance.

[0109] Cyclic performance test

[0110] The cycle performance test method is: charge and discharge current 1C / 1C, voltage range 2.5-4.2V, and cycle number 500 times.

[0111] Test items Initial capacity retention rate (%) Retention rate after 500 cycles (%) Example 1 100 95.11 Example 2 100 94.34 Example 3 100 95.79 Comparative Example 1 100 89.12 Comparative Example 2 100 90.34

[0112] Table 3

[0113] According to the test results of the cycle performance shown in Table 3, the cycle performance of the lithium-ion battery prepared using the lithium-magnesium co-doped silicon-carbon material obtained in Examples 1 to 3 is significantly better than that of Comparative Examples 1 to 2, because the lithium-magnesium co-doped silicon-carbon material obtained in Examples 1 to 3 is doped with magnesium silicate, which reduces the expansion of the material and improves the cycle performance.

[0114] From the above description, it can be seen that the silicon-carbon composite material prepared by the method for preparing the silicon-carbon composite material provided in the embodiment of the present application has the following technical effects:

[0115] (1) Liquid silane is vaporized under a certain vacuum to generate gaseous silane, which is then cracked. Compared with gaseous silane (SiH4), it has the advantages of low cracking temperature, low cost, and high safety factor. In addition, the vaporized deposition of chlorosilane in porous carbon can be used for chlorine doping to improve the electronic conductivity of the material, thereby improving the poor electronic conductivity of the porous carbon itself and improving the fast charging performance.

[0116] (2) By mixing metallic lithium with magnesium oxide to form magnesium silicate and lithium silicate compounds, the structural stability of the material and its initial efficiency are improved. At the same time, the pre-formation of magnesium silicate can reduce the expansion of nano-silicon and improve the initial efficiency and cycle performance of the silicon-carbon material.

[0117] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The method comprises: The porous carbon is transferred to a tube furnace for temperature treatment to obtain a silicon-carbon precursor material; Under a protective atmosphere, the silicon-carbon precursor material, metallic lithium and magnesium oxide powder are mixed to obtain a mixed material; sintering the mixed material; The sintered mixed material is subjected to a deposition treatment to precipitate amorphous carbon on the surface of the sintered mixed material to obtain a silicon-carbon composite material.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The step of transferring the porous carbon to a tube furnace for heating to obtain a silicon-carbon precursor material comprises: The tube furnace is evacuated to 0.09 MPa, and chlorosilane gas is introduced into the tube furnace after evacuation and the temperature is raised to 300-500° C. The pressure of the cavity of the tube furnace after evacuation is maintained at 0.1-1 MPa and kept warm for 1-6 hours to obtain a silicon-carbon precursor material.

3. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: The method further comprises: The chlorosilane is transferred to a reaction kettle and evacuated to a pressure of 0.1 to 0.5 MPa, and then the chlorosilane is heated to 100 to 300° C. to obtain the chlorosilane gas.

4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: The mass ratio of the porous carbon to the chlorosilane is 100:(400-1000).

5. The method for preparing the silicon-carbon composite material according to claim 3 or 4, characterized in that: The chlorosilane is one of propenyltrichlorosilane, trichlorosilane, tetrachlorosilane and dimethylchlorosilane.

6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The mass ratio of the silicon-carbon precursor material, the metallic lithium and the magnesium oxide powder is 100:(1-5):(1-5).

7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The sintering treatment of the mixed material comprises: The mixed material is sintered at a temperature of 900 to 1200°C.

8. The method for preparing the silicon-carbon composite material according to claim 7, characterized in that: The deposition process of the sintered mixed material comprises: Through the vapor deposition method, a carbon source gas is introduced and deposited at a temperature of 700 to 1000° C. for 1 to 6 hours.

9. The method for preparing the silicon-carbon composite material according to claim 8, characterized in that: The carbon source gas includes one of methane, acetylene and ethylene.

10. A lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The negative electrode comprises a silicon-carbon composite material prepared by the method for preparing a silicon-carbon composite material according to any one of claims 1 to 9.